A Comparative Study of Local Financial Autonomy in Italy, France and Morocco - Ait Ouali, Meryem; Boussetta, Mohamed (European Scientific Journal, ESJ, 2017)
Financing local communities relies on a complex network of taxes, subsidies and loans. In the last decade the network has undergone numerous transformations .The reforms implanted in past years changed the systems of public finance substantially. Therefore, financial local autonomy is a term that frequently employed in the literature of federalism and decentralization, but it’s rarely defined conceptually in a careful way to empirical research. Generally it expresses the capacity of local communities to have their own revenue and expenditure budget, distinct from that of the state in which revenue can cover expenses incurred to meet their requirements. Indeed it is a highly valued feature of good governance. This paper is dedicated to a study in theory and practice. Starting with an overview on background of theoretical approach of local financial autonomy, then comparing the experiences of two European countries France, Italy and Morocco in the field. The purpose of this paper is to clarify the meaning of local financial autonomy and give a structured overview of the factors that may potentially influence the liberty of sub national authorities with regard of their own revenue and expenditure budget. Based on indicators and taking into account empirical evidences offered by official statistical datas, established in recent years for evaluating the position of administrative territorial units in relation to central government. The analyses prove that there is no universal model of local public finance applicable to all countries, because each has its own specific historical, cultural and linguistic particularities.